Mazri (Nannorrhops ritchiana (Griff) Aitch.): a remarkable source of manufacturing traditional handicrafts, goods and utensils in Pakistan - Abdullah; Shujaul Mulk Khan; Andrea Pieroni; Zahoor ul Haq; Zeeshan Ahmad (BMC, 2020)
Abstract Background Mazri palm (Nannorrhops ritchiana (Griff) Aitch.) is a member of the family Arecaceae, native to Pakistan, Iran, Afghanistan, Oman, and Saudi Arabia. In Pakistan, it is used since long time for various purposes. This species plays a significant cultural and economic role in the daily lives of many rural areas in Pakistan and adjacent countries. However, the handcrafted products made up of this palm are often mainly known by specific local communities rather than by a broader range of people. Methods Eighty-six structured and semi-structured interviews were conducted from Mazri growing areas, villages, and markets of urban centers during the fieldwork that was conducted in diverse regions of Pakistan. Interviewees included 27 Mazri farmers, 17 locals retaining Traditional Knowledge in handcrafting Mazri palm (12 were men and 5 were women), 23 handicrafts experts (21 were men and 2 were women), and 19 sellers. The age of the informants ranged from 14 to 83 years. Study participants shared detailed information about various traditional utilizations of the Mazri palm. Results Mature leaves of Mazri palm are used to produce mats, baskets, hand fans, hats, cages, hot pots, salt pots, brooms, etc. in the sudy area. Hot pots, salt pots, mats, baskets, and ropes represent highly used items. The mats are used for various purposes like drying grains, performing prayers, sitting, and sleeping. As a whole, 39 different kinds of handcrafted products from the leaves were found. Our findings revealed also that other parts of the plant, ie. petioles, fruits, and bark, have been used, although more rarely, by the locals. The palm uses differ accordingly to the different cultural areas of Pakisitan, thus demonstrating that local cultural heritage significantly informs Traditional Knowledge and practices related to the use of Mazri palm. The findings suggest also that this plant represents a crucial resource for the livelihood of the local communities in dry areas of the western borders of Pakistan, starting right from the coastal areas of Baluchistan up to District Bajaur in the North, where other farming activities there are difficult due to drought conditions. Conclusions Traditional Knowledge about the sustainable utilization of Mazri palm is eroded in Pakistan among the younger generations due to rapid globalization and industrialization processes and appropriate strategies for revitalizing this heritage in a sustainable way should be urgently fostered.